Connectivity modulation during sleep onset, reduction of movement: study via graph theory application to EEG data. Issue 1 (January 2019) - Alù, F.; Vecchio, F.; Miraglia, F.; Gorgoni, M.; Ferrara, M.; De Gennaro, L.; Rossini, P.M.
Abstract : Sleep onset is characterized by specific and orchestrated patterns of frequency and topographical EEG changes. Power analyses and computational assessments of network dynamics have described an earlier synchronization of the centrofrontal areas rhythms and a spread of synchronizing signals from associative prefrontal to posterior areas. We assess how "small world" characteristics of brain networks, as reflected in EEG rhythms, are modified in the wakefulness-sleep transition comparing pre- and post-sleep onset epochs. 40 healthy subjects (20 males;age range 18–29 years) were analyzed. EEG functional connectivity was evaluated in the cortical sources' networks during the wake-to-sleep transition by graph theory application for the evaluation of small-world characteristics. Sleep onset is characterized by a less ordered brain network (as reflected by small world higher values) in sigma band for the frontal lobes indicating stronger connectivity, and a more ordered brain network in low frequency delta and theta bands indicating disconnection on the remaining brain areas. Results depict the timing and topography of the specific mechanisms for the maintenance of functional connectivity of frontal brain regions at the sleep onset, also providing a possible explanation for the prevalence of the frontal-to-posterior information flow directionality previously observed after sleep onset.